Path Research on National Security Education in Applied Private Universities Driven by Artificial Intelligence - Xing, Zengneng (Education Insights, 2025)
National security education serves as a crucial measure to consolidate the foundation of national security and societal stability. For applied private universities, the regular implementation of national security education and adherence to the fundamental mission of moral education and talent cultivation not only constitute core requirements for nurturing qualified professionals who meet contemporary development needs, but also hold significant theoretical and practical value. Against the backdrop of rapid advancements in artificial intelligence technology and its widespread integration into educational fields, the deep integration of AI with national security education in higher education institutions provides new pathways for innovative educational models and quality enhancement in applied private universities. This paper focuses on the application of AI in national security education, systematically analyzing practical challenges currently faced by applied private universities, including outdated teaching content, inadequate practical platforms, and imbalanced faculty structures. To address these critical issues, the study proposes targeted and actionable implementation strategies across four key dimensions: developing adaptive intelligent curriculum systems, establishing diversified smart practical teaching platforms, cultivating high-quality intelligent faculty teams, and improving comprehensive intelligent support systems. These strategic measures aim to significantly enhance the effectiveness and innovation level of national security education, providing robust theoretical support and practical references for advancing the high-quality development of national security education in applied private universities.